Peningkatan Prestasi Belajar dengan Menerapkan Metode Cooperative Learning Model Make A Match dalam Pembelajaran Bahasa Inggris - Suhardi Suhardi (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2022)
The purpose of this study is to find out the application of cooperative learning model make a match method in English learning in improving the learning achievements of students of class X UPW2 SMK Negeri 1 Praya. This research uses a class action research approach. PTK consists of two cycles, each of which consists of planning, implementation, observation, and reflection. The method used is the Cooperative Learning Model Make A Match method. Based on the results of the implementation of actions and the results of student learning evaluations carried out in two cycles, namely in cycle I obtained an average of 68.35 and classical completion of 67.41%. While in cycle II, the average student learning outcome increased to 73.88 and classical completeness increased to 75.17%. This indicates an increase in the percentage from cycle I to cycle II, which is from 67.41% to 75.17%, or there is an increase in success from cycle I to cycle II of about 8%. The findings of this study suggest that the majority of students lack motivation in learning. The use of less than optimal methods makes learning no improvement for students. Based on learning trials conducted using the Cooperative Learning Model Make A Match method, it was obtained that students' motivation and learning achievements increased. Students become active in following learning. Referring to the use of these methods, this research can be used as an effort to increase learning motivation for students.